2022
DOI: 10.1111/rode.12877
|View full text |Cite
|
Sign up to set email alerts
|

The detection dilemma of marginally non‐poor households in poverty alleviation evaluation: Evidence from a linear quantile mixed model

Abstract: Poverty alleviation remains one of the most pressing problems, and China has made considerable advancements toward poverty alleviation in recent years. Considering village as a random effect, this paper proposes a linear quantile mixed model to analyze the effects of household type, village type, and their interactions on household income, suggesting a test of who benefits more or less from anti‐poverty policies. Results indicate that there has been a somewhat unbalanced development between poverty‐stricken ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Scholars have explored the components of the TPA strategy and its implementation mechanism (Li et al, 2022), distilled the TPA strategy from a geographical perspective (Yang & Liu, 2021), and examined the TPA policy process using a relational poverty governance theoretical framework (Xu et al, 2022). Besides, empirical studies have evaluated the impacts of China's poverty alleviation programs, which can be summarized into two main aspects: (1) the overall effectiveness of poverty reduction (Ascher, 2021; Hu et al, 2022); and (2) the impact of specific poverty reduction measure (Liao et al, 2021; Rahman et al, 2021). For instance, Chang et al (2022) found that the TPA program contributed to reducing absolute poverty by increasing incomes.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have explored the components of the TPA strategy and its implementation mechanism (Li et al, 2022), distilled the TPA strategy from a geographical perspective (Yang & Liu, 2021), and examined the TPA policy process using a relational poverty governance theoretical framework (Xu et al, 2022). Besides, empirical studies have evaluated the impacts of China's poverty alleviation programs, which can be summarized into two main aspects: (1) the overall effectiveness of poverty reduction (Ascher, 2021; Hu et al, 2022); and (2) the impact of specific poverty reduction measure (Liao et al, 2021; Rahman et al, 2021). For instance, Chang et al (2022) found that the TPA program contributed to reducing absolute poverty by increasing incomes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to qualitative research methods, methods using geography, economics, statistics, and other disciplines have also been introduced. For example, the G-TOPSIS model [25], logical regression [26], multi-standard model [27], linear quantitative, mixed model [28], correlation analysis [29], space-time statistics [30], and other methods have been used to study the causes of poverty in poverty-stricken villages. The spatial autocorrelation method is used to analyze the distribution characteristics of poverty-stricken villages, establish a comprehensive evaluation mechanism, and establish an early warning mode to prevent poverty-stricken villages from returning to a state of poverty.…”
Section: Introductionmentioning
confidence: 99%